Management of Genetic Activity Through Homoeopathy - DR. H. U. GANGAR (International Journal of Pharma and Bio Sciences, 2010)
Preliminary study on effects of homoeopathic drugs on plants was undertaken at Central Institute for Research on Cotton Technology, Mumbai. It was found that homoeopathic drugs influence genetic activity in the agricultural plant bodies in a big way. Since, there is neither brain nor any central nervous system in plants; known principles/theories of homeopathy cannot be applied here. Under this background, research study on the current subject is undertaken. It is found that medicated water (carrying homeopathic drug) contains intermolecular electrical charges. Present paper explains how these electrical charges perform the act of transferring the energy, (received from original drug), into the concerned gene within the DNA of that cell to trigger the respective gene into the act of activation, acceleration, retardation or turning off its relevant activities. This phenomenon is explained with the help of experiments on cotton, wheat, gram, mungbean etc.